2005
DOI: 10.1159/000086671
|View full text |Cite
|
Sign up to set email alerts
|

Gender Difference of in vivo Skin Surface pH in the Axilla and the Effect of a Standardized Washing Procedure with Tap Water

Abstract: The purpose of our study was to evaluate the axillary skin surface pH and explore potential gender-related differences together with the influence of a washing procedure in healthy subjects. After a run-in period, the skin surface pH was measured in vivo in 10 men and 10 women under standardized conditions in three distinct locations of each axilla (at baseline and up to 6 h after washing). Potential interfering influences were thoroughly excluded. Our study revealed a statistically significant difference in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
11
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 46 publications
2
11
1
1
Order By: Relevance
“…This result is in agreement with others [41] . Although the study on Caucasians aged 26-59 years showed that fe- males have a lower skin surface pH on the forearm and axilla [33,34] , studies here demonstrated that skin surface pH on both the forehead of females aged 13-70 and the forearm of females aged 36-70 was higher than that of males. The difference may be due to sample size and/or the subjects' ethnicities.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…This result is in agreement with others [41] . Although the study on Caucasians aged 26-59 years showed that fe- males have a lower skin surface pH on the forearm and axilla [33,34] , studies here demonstrated that skin surface pH on both the forehead of females aged 13-70 and the forearm of females aged 36-70 was higher than that of males. The difference may be due to sample size and/or the subjects' ethnicities.…”
Section: Discussioncontrasting
confidence: 78%
“…In contrast, the sebum content is significantly higher in younger than in older subjects [29,30] . Although skin surface pH is reportedly higher in females than in males [31,32] , a lower surface pH has also been reported in females [33,34] . Regarding SC hydration, the results are also contradictory, which is largely due to the limited number of subjects studied.…”
mentioning
confidence: 90%
“…This response depended upon the presence of anti-inflammatory cytokine Il-10. In humans, it has been shown that the axillary skin surface pH decreases significantly in women but instead raises in men after simple interventions, such as washing with tap water [44]. The mechanisms underlying such gender related differences in the skin or microbial physiology remain elusive, although they likely reflect the differential effects of sex steroid hormones and associated immunological factors on the skin and mucosal surface secretions found in each gender [45].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the gender differences in skin biophysical properties, previous studies have shown that the skin surface pH in females is higher than that in males, although a lower skin surface pH is also observed in females [1,[13][14][15] . Nevertheless, these studies suggest that there are gender differences in skin surface pH.…”
mentioning
confidence: 96%